Inverse nodal problems for differential operators on graphs with a cycle - Freiling, G.; Yurko, V. A. (Tamkang Journal of Mathematics, 2010)
Inverse nodal problems are studied for second-order differential operators on graphs with a cycle and with standard matching conditions in the internal vertex. Uniqueness theorems are proved, and a constructive procedure for the solution is provided.